(untitled) (World Bulletin of Public Health, 2024)
Kidney cancer, especially renal cell carcinoma, is highlighted as a significant contributor to cancer incidence. Advanced volumetric visualization techniques enable the detection of small renal tumors, facilitate prognostic assessments of tumor progression, and support organ-preserving surgical interventions